2015
DOI: 10.1016/j.tetlet.2015.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of a new bifunctional Cu(I) chelator

Abstract: a b s t r a c tHerein we report an efficient eight-step synthesis of N 1 -(3-(methylthio)propyl)-2-((3-(methylthio)propyl)thio)benzene-1,4-diamine (1) from 6-nitrobenzo [d]thiazole. Incorporation of a nitro rather than a hydroxyl functionality off the aromatic ring serves to enhance conversion during thia-and aza-conjugate additions. Ultimate reduction of the nitro substituent affords a bifunctional Cu(I) chelate in gram-scale quantities for subsequent sensing applications.Ó 2015 Elsevier Ltd. All rights reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We previously demonstrated that this approach can generate excellent fluorescence turn-on responses for Cu(I)-probes in methanol, 20 and it was later adopted by others in the design of Cu(I)-selective fluorescent probes. 21,22 Compared to CTAP-2, probe 4 showed improvements in both contrast ratio (1:100) and fluorescence quantum yield (11%) upon saturation with Cu(I); however, the recovered quantum yield remained more than 5-times below that of reference compound 3 featuring the same fluorophore. Based on the crystal structure of the Cu(I) complex of a closely related acyclic ligand, 20 we suspected that the hydroxymethyl substituents may still produce steric congestion upon Cu(I) coordination, thus weakening the Cu(I)-N interaction.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that this approach can generate excellent fluorescence turn-on responses for Cu(I)-probes in methanol, 20 and it was later adopted by others in the design of Cu(I)-selective fluorescent probes. 21,22 Compared to CTAP-2, probe 4 showed improvements in both contrast ratio (1:100) and fluorescence quantum yield (11%) upon saturation with Cu(I); however, the recovered quantum yield remained more than 5-times below that of reference compound 3 featuring the same fluorophore. Based on the crystal structure of the Cu(I) complex of a closely related acyclic ligand, 20 we suspected that the hydroxymethyl substituents may still produce steric congestion upon Cu(I) coordination, thus weakening the Cu(I)-N interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this modular sensing platform enables any metal ion of any oxidation state to be accurately detected through rational design of the appropriate bifunctional ligand. 21…”
Section: Discussionmentioning
confidence: 99%